Integration and adaptation of foodways toward common acceptable food and food identity formation / Noriza Ishak - Ishak, Noriza (2016)
This study attempt to measure the extent to which integration through food knowledge, food media and food for social events of the Malays, Chinese and Indian foods influenced the adaptation of foodways (preparation and consumption) toward establishment of the common acceptable food and Malaysian food identity formation. This study is structured through a self-administered survey with the individual Malays, Chinese and Indian chefs / cooks who are currently working in the medium / large food catering operations / services and had experienced of preparing and consuming the three Malaysian major ethnic cuisines.